The Bolinao refugee ; Women [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Features Vietnamese refugees landing in Bolinao, Pangasinan ; interview with two activitists, Karina and Betty about their music ; and the interview with different people about women.